ANALYSIS OF TRADITIONAL HEALTH CARE IN THREE COMMUNITY HEALTH CENTERS IN WEST JAVA PROVINCE, INDONESIA, 2018 - Wibowo, Adik; Diniawati, Evita; Sein, Than Tun (UI Scholars Hub, 2019)
The National Traditional Health Care set up three objectives for its implementation at the health centers, whereby health staff to be trained on traditional health and provide accupressure care, able to collect data, register and provide technical guidance to traditional healers and guide individuals in the use of traditional medicine and herbs. This qualitative research aimed to analyze the implementation of traditional health care at 3 subdistrict health centers Ciomas, Ciawi and Caringin in district Bogor. Data was collected through document analysis, observation and indepth inteview. Each health center has trained staff in accupressure but care is hindered by lack of room and community prefers to go to traditional masseur. Data collection, registration and technical guidance to traditional healers exist due to support from local funding. Individual guidance on the use of traditional medicine and herbs do not happen due to no fund for home visits. Traditional health care at health centers to focus on the activity that is working which is data collection, registration and technical guidance to traditional healers. District Health Office Bogor should develop local policy and Standard Operating Procedure for traditional health care at health centers.